Emotional collectives: How groups shape emotions and emotions shape groups. Issue 1 (2nd January 2016) - van Kleef, Gerben A.; Fischer, Agneta H.
Abstract : Group settings are epicentres of emotional activity. Yet, the role of emotions in groups is poorly understood. How do group-level phenomena shape group members' emotional experience and expression? How are emotional expressions recognised, interpreted and shared in group settings? And how do such expressions influence the emotions, cognitions and behaviours of fellow group members and outside observers? To answer these and other questions, we draw on relevant theoretical perspectives (e.g., intergroup emotions theory, social appraisal theory and emotions as social information theory) and recent empirical findings regarding the role of emotions in groups. We organise our review according to two overarching themes: how groups shape emotions and how emotions shape groups. We show how novel empirical approaches break important new ground in uncovering the role of emotions in groups. Research on emotional collectives is thriving and constitutes a key to understanding the social nature of emotions.